A Review of Polyaniline-based Radar Absorbing Materials: Mechanism, Structure, Performance, and Future Applications - Yaaquuta Yusrinaa Salma; Amanda Novita Ramadhani; Nur Fitriani Indah Lestari; Nugrahani Primary Putri (Department of Physics Education, Universitas Mataram, 2026)
Electromagnetic waves caused by the development of radar technology, wireless communications and modern electronic devices has the potential to disrupt the function of the device and impact human health, so solutions are needed such as microwave absorbing materials or radar absorbing materials (RAM) that are light and thin, have high absorption strength, wide absorption band, strong damping, and good stability and environmental resistance. With polyaniline (PANI) as the main focus for microwave absorbing materials because it is a conductive polymer with high conductivity, good chemical stability, low density, and ease of synthesis. , this article will review the latest developments of PANI-based microwave absorbing materials composited with several other materials with a focus on the absorption mechanism, dielectric and magnetic characteristics, and the effect of composite formation on performance improvement. Based on the literature, PANI composites with ferrite, metal oxide, MXene, graphene, and MWCNT show reflection loss (RL) up to −88.8 dB with effective the bandwidth reaches 14.6 GHz at a thin thickness of 1–3 mm. This performance improvement results from the synergy between dielectric and magnetic losses through the mechanisms of multiphase interface polarization, Debye relaxation, natural magnetic resonance, and impedance matching. optimal matching. With its lightweight, flexible characteristics and wide frequency range operation (S band– Ku band), PANI-based composites are excellent candidates for radar absorbing material (RAM), electromagnetic shielding (EMI shielding), and stealth technology applications in defense systems and modern electronic devices.